Harmony of Homeschooling and Islamic Education: Exploring Opportunities and Challenges in the Indonesian Context - Hunaida, Wiwin Luqna; Halim, Abdul; Hadiyansyah, Dhuha (Jurnal Tarbiyatuna, 2024)
This research explores innovations and challenges in the integration of Islamic religious education with the homeschooling model in Indonesia, focusing on Homeschooling KakSeto and Sekolah Murid Merdeka. Using a qualitative approach through case studies, this study involved six homeschooling families and collected data through observation, in-depth interviews, and questionnaires to 44 parents. The results of the study identified innovations in Islamic education such as the use of technology, active learning, and integrated curriculum development. Homeschooling offers curriculum flexibility, closer family relationships, and teaching religious values ​​that are more in line with family beliefs. However, there are challenges such as lack of child socialization, financial problems, concerns about homeschooling diploma, and difficulty finding the right curriculum. This study provides insight into the opportunities and barriers of homeschooling in Islamic education, and suggests the need for training and policy support for parents who choose homeschooling.